5-Chloro-8-hydroxy-6-methyl-1,4-naphthoquinone - Tan, Daniel Teoh-Chuan (International Union of Crystallography, 2009)
The molecule of the title compound, C(11)H(7)ClO(3), is planar, with a maximum deviation of 0.0383 (10) Å from the naphthoquinone plane. An intramolecular O—H⋯O hydrogen bond generates an S(6) ring motif. The crystal packing is stabilized by intermolecular C—H⋯O hydrogen bonds. Short intramolecular Cl⋯O [2.8234 (8) Å] and O⋯O [2.5530 (11) Å], and intermolecular Cl⋯Cl [3.2777 (3) Å] contacts further stabilize the crystal structure.